Directed Biosynthesis of New to Nature Alkaloids in a Heterologous Nicotiana benthamiana Expression Host - Boccia, Marianna; Grzech, Dagny; Lopes, Adriana A.; O’Connor, Sarah E.; Caputi, Lorenzo (Frontiers in Plant Science, 2022)
Plants produce a wide variety of pharmacologically active molecules called natural products. Derivatization of these natural products can modulate or improve the bioactivity of the parent compound. Unfortunately, chemical derivatization of natural products is often difficult or impractical. Here we use the newly discovered biosynthetic genes for two monoterpene indole alkaloids, alstonine and stemmadenine acetate, to generate analogs of these compounds. We reconstitute these biosynthetic genes in the heterologous host Nicotiana benthamiana along with an unnatural starting substrate to produce the corresponding new-to-nature alkaloid product.